1994
DOI: 10.1042/bj3030441
|View full text |Cite
|
Sign up to set email alerts
|

Co-purification of a protein tyrosine phosphatase with activated somatostatin receptors from rat pancreatic acinar membranes

Abstract: We have previously shown that somatostatin promotes the stimulation of a membrane tyrosine phosphatase activity in pancreatic cells. To gain insight into the mechanism of somatostatin action, we purified somatostatin-receptor complexes from somatostatin 28-prelabelled rat pancreatic plasma membranes by immunoaffinity chromatography using immobilized antibodies raised against the N-terminal part of somatostatin 28, somatostatin 28 (1-14), which is not involved in receptor-binding-site recognition. After SDS gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…Furthermore, in pancreatic cells that highly expressed endogenous sst2, SHP-1 copurified with somatostatin receptors (15). To investigate whether SHP-1 interacts with sst2, we stably coexpressed SHP-1 and sst2 in CHO cells.…”
Section: Shp-1 Associates With Sst2 In Resting Cho/sst2-shp-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in pancreatic cells that highly expressed endogenous sst2, SHP-1 copurified with somatostatin receptors (15). To investigate whether SHP-1 interacts with sst2, we stably coexpressed SHP-1 and sst2 in CHO cells.…”
Section: Shp-1 Associates With Sst2 In Resting Cho/sst2-shp-1mentioning
confidence: 99%
“…Incubation of cells expressing sst2 with the PTPase inhibitor, vanadate, prevented both effects suggesting that a PTPase may be implicated in the negative growth signal induced by activation of sst2. In addition, we demonstrated that a PTPase of 70 kDa, identified as SHP-1, copurified with membrane somatostatin receptors (15) from pancreatic acinar cells that highly expressed sst2 receptor subtype (16). Taken together, these results suggest that SHP-1 may be a candidate for sst2-mediated early signaling events.…”
mentioning
confidence: 99%
“…Our data, showing that BIM inhibits MAP kinase activity stimulated by both IGF-1 and carbachol, indicate that BIM acts at a very early post-receptor level and at some step common to the signalling cascade initiated by both tyrosine kinase and Gprotein coupled receptors leading to MAP kinase activation. Having excluded an involvement of CAMP, Ca2+ and pH, a tyrosine phosphatase activity, which has recently been found to be associated with SST receptors [23,24], might be suggested as responsible for the analogue's action.…”
Section: Sy5y Cellsmentioning
confidence: 99%
“…This suggests a mechanism for somatostatin action upstream of PKA and PI 3-kinase and indicates the inhibitory potential of somatostatin, which is able to counteract PKA-dependent and -independent proliferative effects. FRTL-5 thyroid cells express the somatostatin receptor SSTR2 (8), and this receptor can be coupled to several downstream effectors such as adenylyl cyclase or protein-tyrosine phosphatases (55,56). Moreover, TSH increases intracellular cAMP levels (28,43).…”
Section: Kip1mentioning
confidence: 99%